Peran Corporate Social Responsibility dan Good Corporate Governance Terhadap Kinerja Keuangan Pada Perbankan di Indonesia Periode 2014-2019 - Idayanti, Rini; Hasni, Hasni (IAIN Ambon, 2022)
AbstractAssessing the company's financial performance is very important to do to determine the health condition of banks, especially when the economic crisis occurs. Return on Assets (ROA) is one of the ratios for measuring financial performance. Where ROA is defined as the effectiveness of the company in generating profits by utilizing its assets. This study aims to examine the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on financial performance as proxied by Return on Assets (ROA). With a quantitative approach and using panel data regression analysis. The population used in this research is banking listed on the Indonesia Stock Exchange (BEI) 2014-2019, the sample used in this study was selected by purposive judgment sampling, the results of this study indicate that social responsibility (Corporate Social Responsibility) has a significant effect on Return on Assets (ROA) and Return on Equity (ROE). Meanwhile, Good Corporate Governance (GCG) has no significant effect on Return on Assets (ROA) and Return on Equity (ROE).Keyword :Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Return on Asset (ROA), Return on Equity (ROE). AbstrakMenilai Kinerja Keuangan Perusahaan sangat penting dilakukan untuk mengetahui kondisi kesehatan perbankan terutam44a saat krisis ekonomi terjadi, Return on Assets (ROA) merupakan salah satu rasio untuk pengukuran kinerja keuangan. Dimana ROA didefinisikan sebagai efektivitas perusahaan dalam menghasilkan laba dengan memanfaatkan aktiva yang dimiliki. Penelitian ini bertujuan untuk menguji pengaruh Corporate Social Responsibility (CSR) dan Good Corporate Governance (GCG) terhadap kinerja keuangan yang diproksikan pada Return on Asset (ROA). Dengan pendekatan kuantitatif dan menggunakan analisis regresi data panel. Populasi yang digunakan dalam penelitian ini adalah perbankan yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2014-2019, sampel yang digunakan dalam penelitian ini dipilih secara purposive judgment sampling, Hasil penelitian ini menunjukkan bahwa tanggung jawab sosial (Corporate Social Responsibility) berpengaruh signifikan terhadap Return on Assets (ROA) dan Return on Equity (ROE). Sedangkan Good Corporate Governance (GCG) tidak berpengaruh signifikan terhadap Return on Assets (ROA) dan Return on Equity (ROE).Kata Kunci : Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Return on Asset (ROA), Return on Equity (ROE).